2023
DOI: 10.1038/s41377-023-01142-1
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond electron microscopy of relativistic electron bunches

Abstract: The development of plasma-based accelerators has enabled the generation of very high brightness electron bunches of femtosecond duration, micrometer size and ultralow emittance, crucial for emerging applications including ultrafast detection in material science, laboratory-scale free-electron lasers and compact colliders for high-energy physics. The precise characterization of the initial bunch parameters is critical to the ability to manipulate the beam properties for downstream applications. Proper diagnosti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…On the basis of this understanding, it is shown that, as the bunch propagates further into the density downramp (Fig. 2, B9 and B10), its transverse sizes gradually increase due to the weakening of the plasma focusing force (31,46). Additionally, the transverse scale of the wakefield (represented by the trailing periodic bright-dark pattern) also increases along with the drive electron beam, behaving as a quasi-linear beam-driven plasma wave (47).…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…On the basis of this understanding, it is shown that, as the bunch propagates further into the density downramp (Fig. 2, B9 and B10), its transverse sizes gradually increase due to the weakening of the plasma focusing force (31,46). Additionally, the transverse scale of the wakefield (represented by the trailing periodic bright-dark pattern) also increases along with the drive electron beam, behaving as a quasi-linear beam-driven plasma wave (47).…”
Section: Resultsmentioning
confidence: 91%
“…This was confirmed by slightly reducing the input laser energy to avoid ionization injection, which revealed that the strength of the wakefield was notably weaker compared to that observed with an injected electron beam. Furthermore, the elliptical hollow structure preceding the wakefield was recently discovered to resemble the transverse charge-density distribution of the electron bunch (31). On the basis of this understanding, it is shown that, as the bunch propagates further into the density downramp (Fig.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations